(untitled) (Research, Society and Development, 2020)
The Cerrado biome is a source of chemical molecules with great medicinal potential. The substances extracted from pequi, the fruit of Caryocar brasiliense, have antiparasitic, antioxidant, and antineoplastic properties. Canine osteosarcoma is a highly aggressive and metastatic bone tumor, not very responsive to current chemotherapy modalities. This study aimed to show the effects of the ethanol extract of pequi peel (EEPP) on canine osteosarcoma cells, in addition to suggesting a metabolic route that explains the action of the extract. D-17 cells were seeded and exposed to EEPP at concentrations of 0, 10, and 100 µg/mL. After treatment, the cell nuclei were marked with DAPI and quantified using fluorescence microscopy. The expression of proteins p53, Ki-67, Bcl-2, Akt, AMPK, and mTOR was analyzed using immunocytochemistry. By using DAPI, we found a reduction in the number of quantified nuclei, time, and dose-dependent. The labeling of p53, Ki-67, and Bcl-2, antibodies decreased in groups exposed to EEPP. The opposite was observed with Akt, AMPK, and mTOR antibodies, where the protein was not found in the control group but was expressed in groups exposed to EEPP. We suggest a possible metabolic route where EEPP promotes cell death and cell cycle control in D-17 cells.